Assessment of frailty in Alzheimer's: a literature review. (2nd July 2019) - Smith, Kirsty; Wallington, Sophie
Abstract : As the UK's older population continues to rise, the more likely it is for practice nurses to encounter patients living with Alzheimer's and frailty.Kirsty Smith andSophie Wallington explore the definitions and models of frailty available in medical literature As a consequence of an ageing global population, it is likely that encounters between health professionals and frail patients will rise. Patients with both suspected frailty and Alzheimer's disease are frequently encountered in primary care. There are links and overlaps between these disease states; however, the key theories and models of frailty propose some contradictions. This review of the definition, theories and models of frailty, and relevance to patients with Alzheimer's disease will add a quality, evidence-based approach to the assessment of frailty in patients in primary care living with Alzheimer's disease.